Trigger Topics: Where Religion & Health Care Intersect - Lynn Stoller; Eliza Blanchard; Mark Fowler (Association of American Medical Colleges, 2015)
Abstract Introduction Medical education increasingly recognizes that cultural competence is an important component of patient care. However, religion is an aspect of culture that still often goes unaddressed in medical education. The knowledge and skill sets presented in this course provides instruction for preservice physicians on how to address the topic of religion when it impacts patient care and/or patient decision-making. Addressing the religious beliefs of patients as it relates to their health care is an essential component of patient centered care and improves patient satisfaction. This resource addresses this gap in medical education. The course content examines 15 trigger topics where religion often emerges in a health care setting so that medical students can be prepared and proactive in addressing the topic of religion with their patients. Methods This 90-minute module includes didactic information for an educator to present to a class of students accompanied by case study discussions and activities that can be used to reinforce learning. The materials comprise two documents: a facilitator's guide and an accompanying PowerPoint presentation. The PowerPoint is designed to be presented in class and the facilitator's guide provides detailed instructions and helpful strategies for the facilitator on how to effectively convey the information in addition to providing numerous case study discussion activities to reinforce learning. Two examples and one detailed case study discussion activity are included in this module for each of the trigger topics. Results A version of this curriculum was incorporated into a course titled End of Life Care at Hofstra North Shore-LIJ School of Medicine. In an evaluation the medical students completed after the course, 60% of students agreed or strongly agreed with the following statement: "Session content enhanced my knowledge and/or skills." In addition, 70% agreed or strongly agreed that the "session was engaging." Discussion This module takes a thematic approach because, given the diversity between and within different faith traditions, it is unrealistic to expect health care providers to be familiar with the diversity of patient religious beliefs and practices that they encounter on a daily basis. Moreover, teaching medical students what all Muslims, Christians, Hindus, etc., believe ignores the diversity within these groups and can lead to false assumptions and stereotyping. A more effective and practical strategy of understanding how a patient's religious beliefs may impact his/her care is by learning to identify certain themes across faith traditions where religion emerges, along with effective strategies and skills for addressing challenges when they emerge.